Differences in antitumor effects of various statins on human pancreatic cancer - Gbelcová, Helena; Lenícek, Martin; Zelenka, Jaroslav; Knejzlík, Zdenek; Dvoráková, Gabriela; Zadinová, Marie; Poucková, Pavla; Kudla, Michal; Balaz, Peter; Ruml, Tomás; Vítek, Libor (International journal of cancer, 2008)
Statins are widely used for the treatment of hypercholesterolemia. However, their inhibitory action on HMG-CoA reductase also results in the depletion of intermediate biosynthetic products, which importantly contribute to cell proliferation. The aim of the present study was to compare the effects of the individual commercially available statins on experimental pancreatic cancer. The in vitro effects of individual statins (pravastatin, atorvastatin, simvastatin, lovastatin, cerivastatin, rosuvastatin and fluvastatin) on the viability of human pancreatic cancer were evaluated in CAPAN-2, BxPc-3 and MiaPaCa-2 cell lines. The in vivo experiments were performed on nude mice xenotransplanted with CAPAN-2 cells. The mice received oral treatments either with a placebo, or with the statins mentioned earlier in a daily dose corresponding to a hypocholesterolemic dose in humans. The effect of these statins on the intracellular Ras protein, trafficking in MiaPaCa-2 transfected cells, was also investigated. Substantial differences in the tumor-suppressive effects of all statins were detected in both in vitro and in vivo experiments. While simvastatin exerted the highest tumor-suppressive effects in vitro, rosuvastatin (p = 0.002), cerivastatin (p = 0.002) and fluvastatin (p = 0.009) were the most potent compounds in an animal model. All statins (except pravastatin) inhibited intracellular Ras protein translocation. In summary, substantial tumor-suppressive effects of various statins on the progression of experimental pancreatic adenocarcinoma were demonstrated, with marked differences among individual statins. These results support greatly the potential of statins for the chemoadjuvant treatment of pancreatic cancer.
Keywords: nádorové buněčné linie; Neoplasm Transplantation; polymerázová řetězová reakce; Polymerase Chain Reaction; DNA primery; nádory slinivky břišní; adenokarcinom; Mice; Cell Line, Tumor; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Base Sequence; sekvence nukleotidů; Mice, Nude; zvířata; Humans; statiny; transplantace nádorů; Pancreatic Neoplasms; myši nahé; myši; DNA Primers; Adenocarcinoma; lidé; Animals